How to evaluate lifelong learning skills of healthcare professionals: a systematic review on content and quality of instruments for measuring lifelong learning - Monica H. M. Verkooijen; Anne A. C. van Tuijl; Hiske Calsbeek; Cornelia R. M. G. Fluit; Petra J. van Gurp (BMC Medical Education)
Abstract Background Having lifelong learning skills is a necessity for healthcare professionals. To evaluate these skills, sound instruments are needed. Those working in healthcare of medical educating looking for a suitable instrument to evaluate lifelong learning (LLL) skills in healthcare professionals are faced with a multitude of definitions and operationalizations of the concept of LLL. A systematic review was performed to analyze the methodological quality and content of instruments measuring LLL for professionals. Methods A systematic search of literature published until October 2023 in the electronic databases MEDLINE, CINAHL, PsycINFO, ERIC, Sociological Abstracts, EMBASE, and Web of Science was conducted. English articles describing the development, validation or use of an instrument measuring lifelong learning for professionals working in a professional context were included. A data extraction form was developed to evaluate the content and methodological quality of the instruments. The STORIES statement was used to support reporting this review. Results The search revealed 85 articles on 18 questionnaires, no qualitative instruments were found. The instruments covered a range of settings, for example the Jefferson Scale of Physician LLL (JSPLL) covered healthcare and the Effective LLL Inventory (ELLI) covered education. Most instruments provided evidence on content validity and internal consistency, other aspects of validity were examined less frequently. Furthermore, the way that LLL was defined varied greatly, also great variety in the constructs that were defined in the instruments was found. Most instruments lacked a clear description of how the dimensions and items were formalized. Conclusions There is a need for LLL instruments that provide more evidence on their validity and put greater emphasis on the development of the definition and operationalization of LLL. Furthermore, there is a need for a better understanding of how to interpret and use the results of the instruments. It is recommended to take a critical look at these constructs before selecting an instrument. This will help all those involved in the training and working environment of healthcare professionals in evaluating lifelong learning skills in their context. Registration PROSPERO registration number: CRD42019134804